Extraterritorial application of the GDPR: Promoting European values or power? - Oskar Josef Gstrein; Andrej Janko Zwitter (Internet Policy Review, 2021)
This article examines whether the territorial scope of the EU General Data Protection Regulation promotes European values. While the regulation received international attention, it remains questionable whether provisions with extraterritorial effect support a power-based approach or a value-driven strategy. Developments around the enforceability of a 'right to be forgotten', or the difficulties in regulating transatlantic data flows, raise doubts as to whether unilateral standard setting does justice to the plurality and complexity of the digital sphere. We conclude that extraterritorial application of EU data protection law currently adopts a power-based approach which does not promote European values sustainably. Rather, it evokes wrong expectations about the universality of individual rights.
Keywords: 300; European values; GDPR; Privacy; Extraterritoriality